Dampak Covid 19 terhadap Pelayanan Perizinan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Jambi Tahun 2021 - Pantun Bukit; Fakhrul Rozi Yamali; Hana Tamara Putri; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2022)
The impact of the Covid-19 Pandemic occurred in all fields including public services in Jambi Province since March 2020 until now. Licensing and non-licensing services are forced to be limited and closed to several agencies, including the Jambi Province Investment and Integrated Services Office (DPM-PTSP), performing online services is preferred to make it easier for people to get access to public services. Community Satisfaction Index research on the services of the Jambi Province Investment and Integrated Services Office is carried out by survey methods supported by quantitative descriptive analysis. The survey method is used to determine the level of user satisfaction of DPMPTSP services in Jambi Province in 2021. The community satisfaction index (IKM) in the Licensing Unit Service of the Investment Office and One-Door Integrated Services of Jambi Province in the first semester of 2020 was worth 90,278 for the value of IKM after being converted. The amount of the IKM value indicates that the quality of service is still at level A and the performance of the DPM-PTSP licensing service unit of Jambi Province is very good.